2010
DOI: 10.1017/s1742758410000378
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficacy of CalneemTM oil against the tropical warehouse moth Ephestia cautella (Lepidoptera: Pyralidae) in stored maize

Abstract: The tropical warehouse moth Ephestia cautella (Walker) is an important storage pest of maize grain. The control of this major moth pest relies heavily on the use of synthetic insecticides. We assessed the biological efficacy of a commercial neem oil (Calneem oil) against E. cautella in the laboratory, using the common grain protectant Actellic as a positive control. Contact toxicity, repellency, effects on oviposition, development and grain damage were assessed. The assays were conducted by treating 100 g of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
(8 reference statements)
3
16
0
1
Order By: Relevance
“…These results were similar to those of DAD et al (2011), who observed reduced fecundity, limitation in the number of deposited eggs and totally inhibited eclosion after the treatment with neem in Musca domestica larvae. Research, v.194, p.237-244, 1978. Studies with azadirachtin or neem oil on Lepidoptera also demonstrated changes in fertility and fecundity of S. littoralis (PINEDA et al, 2009), anti-oviposition and ovicidal effects against E. cautella (SHEHU et al, 2010), ovicide with changes in the embryonic development against D. saccharalis (SILVA et al, 2013) and extended embryonic period in D. saccharalis (OLIVEIRA et al, 2013).…”
Section: Residual Effect Of Neem Oil Extract In Stages Subsequent To mentioning
confidence: 97%
See 2 more Smart Citations
“…These results were similar to those of DAD et al (2011), who observed reduced fecundity, limitation in the number of deposited eggs and totally inhibited eclosion after the treatment with neem in Musca domestica larvae. Research, v.194, p.237-244, 1978. Studies with azadirachtin or neem oil on Lepidoptera also demonstrated changes in fertility and fecundity of S. littoralis (PINEDA et al, 2009), anti-oviposition and ovicidal effects against E. cautella (SHEHU et al, 2010), ovicide with changes in the embryonic development against D. saccharalis (SILVA et al, 2013) and extended embryonic period in D. saccharalis (OLIVEIRA et al, 2013).…”
Section: Residual Effect Of Neem Oil Extract In Stages Subsequent To mentioning
confidence: 97%
“…Mean ± standard error of longevity, emergency rate, morphological abnormalities and mortality of adults emerged of young pupae and old pupae of D. saccharalis treated with neem oil extract in experimental conditions. rate (KHAN et al, 2007;SHEHU et al, 2010). Artificial diets containing different concentrations of the aqueous extract of A. indica also decreased the survival of D. saccharalis caterpillars (MAZZONETTO et al, 2013).…”
Section: Residual Effect Of Neem Oil Extract In Stages Subsequent To mentioning
confidence: 99%
See 1 more Smart Citation
“…Their activity is quickly reduced by light; they are only slightly toxic to mammals, and are compatible with the natural foes of several insects [7][8][9]. Studies on the effects on insects treated or fed with azadirachtin have reported growth inhibition; death of caterpillars during ecdysis; prolongation of the larval stage; deformation of caterpillars and adults; decrease in longevity, fecundity and fertility [10][11][12][13]. Azadirachtin in neem oil has selective effects on insects, mostly with respect, impaired feeding and interrupted growth [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…neem oil directly applied to Lepidoptera eggs, are rare. Some studies have documented the effects on oviposition, following treatment of caterpillar adults or pupae [12,13,17,18]. Ovicide effects of neem solution were reported after application to egg masses of different ages in Diatraea saccharalis F., 1794 (Lepidoptera: Crambidae), but subsequent effects on the development of caterpillars have not been demonstrated [19].…”
Section: Introductionmentioning
confidence: 99%